Academic achievement as a predictor of success in bachelor of pharmacy degree examinations: Preliminary findings - Othman, Noordin; Zin, Che Suraya; Bux, Siti Halimah (2012)
At the International Islamic University Malaysia (IIUM), students are enrolled into a bachelor degree program after successfully completing a two-year foundation study. Recently, the mode of entry into the bachelor of pharmacy degree in Malaysian has been questioned. No evidence is available on the appropriateness of entry standards set by the Pharmacy Board of Malaysia. We aimed to assess the relationship between the academic achievement in foundation studies and the first year of pharmacy degree. This cross-sectional study evaluated the academic achievement of 90 students who were enrolled in bachelor of pharmacy program during 2010/2011 academic year. Of 90, 30 (33%) were males and 60 (67%) were females. The cumulative grade point average (CGPA) of these students at the end of foundation studies and at the end of semester one examination of first year bachelor of pharmacy was compared and analyzed. Descriptive statistics were produced. Pearson's correlation test was used to assess the correlation of academic achievement in both study periods. We found that none of students obtained grade A in both groups. Only a few students obtained grade A- (foundation, 5.5% (n=5/90), first year, 1.1% (n=1/90). There were 38.8% (n=35/90) and 10% (n=9/90) of students obtained grade B+ during foundation and first year study respectively. Most students in both groups obtained grade B (foundation, 55.5% (n=50/90), first year 35.5% (n=32/90)). The academic achievement in foundation study correlates (r=0.65, p<0.05) with the achievement in the first year of studies in the IIUM. The students’ achievement in the foundation study was positively correlated with the achievement in the first year of bachelor of pharmacy degree study. Although the findings are preliminary, they suggest that strict entry requirement policy should be in place to ensure the highest quality of pharmacy graduates.